Effects on Postural Kinematics of Performing a Cognitive Task During Upright Standing. Issue 4 (August 2020) - Hagio, Kohtaroh; Obata, Hiroki; Nakazawa, Kimitaka
The execution of cognitive tasks is known to alter postural sway during standing, but the underlying mechanisms are still debated. This study investigated how performing a mental task modified balance control during standing. We required 15 healthy adult males to maintain an upright stance under conditions of simply relaxing and maintaining normal quiet standing (control condition) or while performing a secondary cognitive task (mental arithmetic). Under each condition, we measured the participants' center of pressure and used kinematic measurements for a quantitative evaluation of postural control modulation. We calculated the standard deviation of the joint angles (ankle, knee, and hip) and the estimated joint stiffness to measure joint mobility changes in postural control. To estimate the kinematic pattern of covariation among these joints, we used uncontrolled manifold analysis, an assessment of the strength of multijoint coordination. Compared to normal standing, executing the cognitive task while standing led to reduced movements of the ankle and hip joints. There were no significant differences in ankle stiffness or uncontrolled manifold ratios between the conditions. Our results suggest that when performing a secondary cognitive task during standing, neither changes in the modification of stiffness nor the strength of multijoint coordination (both of which preserve the center of mass position) explains changes in postural sway.